MANAJEMEN PENYELENGGARAAN UJI KOMPETENSI KEAHLIAN SMK SE KABUPATEN SLEMAN (JURNAL ILMIAH TUT WURI HANDAYANI, 2013)
This research is conducted to know how management principles: planning, organizing, actuating and controlling are implemented in the assessment of skill competency of Vocational Schools (SMK) students in Sleman. This research is also aimed to reveal howm the preparation of assessment is verified. Besides, this research is done to know the acknowledgement of Competency Certificates of SMK students by the industry.The research held in 53 State and Private Vocational Schools in Kabupaten Sleman using the simple quantitative approach and qualitative approach. The researcher distributed questioners containing questions about the objectives of the research as mentioned above. The researcher continued the research using the qualitative approach in 2 (two) State Vocational Schools and 2 (two) Private Vocational Schools. The qualitative approach was done by examining documents and interviewing personnel involved in the assessment of skill competency.The result of this research showed that in general, all Vocational Schools have implemented the management principles, planning, organizing, actuating and controlling, but it is not yet done in detail. The verification of readiness of Vocational Schools to carry on competency assessment has also been done following the guidance. The verification was done to check the preparation of schools to carry on assessment either the equipment, the adequacy in number, the specification, the materials needed and budgeting. Certificates of Competency owned by Vocational School graduates are forms of acknowledgement toward their competencies, however they still have to take a test or selection whenever they apply for jobs as new workers. The reason is that the number of applicants is bigger than the number of workers needed.